PENGEMBANGAN MEDIA POP UP BOOK PADA PEMBELAJARAN TEMATIK TERPADU KELAS IV SEKOLAH DASAR - Rossa, Rona; Insani, Fitri (Jurnal Riset Pendidikan Dasar Dan Karakter, 2024)
This study was motivated by issues such as students’ concentration being focused mainly at the beginning of lessons and the lack of creative and innovative learning media. Existing media at school were still simple and failed to attract students' interest. To address this, a pop-up book was developed—paper-based media that displays three-dimensional objects when opened. This media was designed for the theme “Caring for Living Beings” in Grade IV of elementary school. The research employed the 4-D development model (Define, Design, Development, Disseminate). Validation results showed that the media was highly valid in terms of design (94.2%) and content (95.4%), and fairly valid in language (77%). Practicality tests yielded 98% from teachers and 85.4% from students, categorized as very practical and practical, respectively. The effectiveness test scored 87%, indicating high effectiveness. Thus, the pop-up book media is considered very valid, practical, and effective for use in integrated thematic learning